Developing competitive strategies among entrepreneurial managers in Nigeria using DEMATEL approach - Olamitunji Dakare (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The study is aimed at investigating how entrepreneurial managers in Nigeria can better identify and distinguish the cause-and-effect relationship amongst the components of competitive strategies. The components of competitive strategies among entrepreneurial ventures were classified into three components and eleven criteria after a review of the literature. The study applied the Decision-Making Trial and Evaluation Laboratory (DEMATEL) model to identify and describe the cause-and-effect relationship amongst the components of competitive strategies. The findings revealed that in prioritizing the importance of criteria and cause-and-effect relationship among criteria under the three core components, emphasis on being ahead of the competition, strong sales force and R&D expenditure for process innovations were the most critical criteria. Furthermore, the findings have, however, showed that emphasis on being ahead of the competition was the most important criterion in the adjustment of components of competitive strategies among entrepreneurial ventures in Nigeria. Therefore, to develop a highly competitive strategy among entrepreneurial ventures, entrepreneurial managers will need first to develop the culture and attitude of being ahead of the competition in line with their managerial propensities which, in turn, will help them to create strategic moves that can give a high payoff in the midst of competitive pressures from rivals.
Keywords: M13; 330; Competitive strategy; capabilities; entrepreneurial ventures; Nigeria; DEMATEL